2022
DOI: 10.2147/dmso.s346411
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Advanced Glycation End Products Shift the Gut Microbiota Composition and Induce Insulin Resistance in Mice

Abstract: This study aimed to explore the associations between gut microbiota characteristics and glycometabolic profiles in mice fed diets high in advanced glycation end products (AGEs). Methods: C57BL/6 mice were exposed to a heat-treated diet or exogenous AGEs for 24 weeks, and glucose metabolism was assessed via the intraperitoneal glucose-tolerance test (IPGTT). Serum AGE and lipopolysaccharide-binding protein (LBP) levels were quantified using ELISA kits. 16S rDNA sequencing was performed to analyze the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…To date, the current literature has questioned many findings from animal and human studies due to the unreliability of the methods used for AGEs measurements. Most studies in the past predominantly measured AGE levels in foods using ELISA [ 61 , 62 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ] instead of ultraperformance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS), which is currently considered the gold standard for AGE measurements [ 19 , 104 ]. In addition, many studies focused on producing high-AGE and low-AGE diets using high and low baking (heat-treated) methods or changing the cooking technique (boiling, poaching instead of grilling, frying) to adjust the AGE concentrations in foods.…”
Section: Ages Oxidative Stress and Inflammation In The Gutmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the current literature has questioned many findings from animal and human studies due to the unreliability of the methods used for AGEs measurements. Most studies in the past predominantly measured AGE levels in foods using ELISA [ 61 , 62 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ] instead of ultraperformance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS), which is currently considered the gold standard for AGE measurements [ 19 , 104 ]. In addition, many studies focused on producing high-AGE and low-AGE diets using high and low baking (heat-treated) methods or changing the cooking technique (boiling, poaching instead of grilling, frying) to adjust the AGE concentrations in foods.…”
Section: Ages Oxidative Stress and Inflammation In The Gutmentioning
confidence: 99%
“…Yacoub et al [ 101 ] conducted a randomised open-label-controlled trial, looking at the association between the gut microbiota and the consumption of dietary AGEs in patients with end-stage renal disease. Their study indicated that a one-month dietary AGE restriction was associated with a decline in the relative abundance of Prevotella copri and Bifidobacterium animalis and with an increase in the relative abundance of Alistipes indistinctus, Clostridium citroniae, Clostridium hathewayi , and Ruminociccus gauvreauii [ 101 , 102 , 151 , 152 ]. The increase in Alistipes indistinctus is not likely beneficial, as it is recognised to be highly pathogenic due to its strong association with colitis and tumorigenesis in mice [ 153 ].…”
Section: Ages and The Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The most well studied AGEs include Nε-(carboxymethyl)lysine (CML), Nε-(1-carboxyethyl)lysine (CEL) and methylglyoxal-derived hydroimidazolone-1 (MG-H1). In vitro and in vivo studies show that ingested AGEs can induce an inflammatory response [ 2 , 3 , 4 , 5 ] and affect microbial growth [ 5 , 6 , 7 , 8 , 9 , 10 ]. Furthermore, previous human studies showed that a diet high in dietary AGEs is associated with low-grade inflammation, endothelial dysfunction and insulin resistance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary changes can have a considerable and sustained effect on the composition of the microbiome, and alterations in the microbiome, in turn, may influence the absorption, breakdown, and storage of nutrients. 11 , 18 , 20 Additionally, compositional differences in gut microbiota contribute to individual differences in the metabolic responses to specific foods. 21 , 22 These differences have been associated with differential weight loss in response to certain diets.…”
Section: Introductionmentioning
confidence: 99%